TRADISI MENGHIDUPKAN MALAM NISF SHA’BAN DI MASYARAKAT DAN PENGARUH MASYARAKAT URBAN: Studi Living Quran Di Masjid Miftahul Jannah Rw11 Desa Sindang Pakuon, Kecamatan Cimanggung, Kabupaten Sumedang - Dindin Moh Saepudin; Dadan Rusmana (UIN Siber Syekh Nurjati Cirebon, 2019)
Nisf Sha’ban has become a tradition in Indonesian society as a day when people flock to fill mosques, musala to read letters of Ya>si>n, prayer sunnah taubat, salawat, dhikr, read the Koran and so on, one of them at the Mosque of Miftahul Jannah, Rt.01 / Rw. 11, Desa. Sindang Pakuon, Kec. Cimanggung, Kab. Sumedang, so that the authors are interested in examining how the reading and reading of Sha’ba>n is improved by the community with a living approach to the Koran theory. The results of this study indicate that the tradition of Nisf Sha’ban in the hamlet of Cimande, the Mosque of Miftahul Jannah shows one form of reception of Islamic societies towards the Qur‘an. With this, the Qur‘an is not only a reading material, but also as a means to connect the relationship between fellow Cimande Hamlets, with the existence of traditions like this that have been ingrained when the Miftahul Jannah Mosque has been established, according to traditional writers. this kind is a model of Islamic Nusantara which is rich in tradition and culture.